The recent trend to deal with grammatical errors written to the students of the International Islamic University Malaysia - Yani, Achmad; Omar, Zakaria; Yousif, Khalid Osman; Kama, Nonglaksana (2014)

(untitled)
This descriptive research and analysis, we will follow in conducting it analysis method error, we will fox practical in this paper on the grammatical errors of the sample through a placement exam first previous 2013 which it done for those sample. We fox on these mistakes syntax by the mistake of using (ال the), and mistake of changing wards from male to female, and also we foxed on the mistake of using Arabic preposition during writing essay. It should be noted that the new benefit in this paper that it will contain drills which solve the problems of the students that we have mentioned in the abstract.